Evaluating extracurricular educational activities: Perspectives from management staff and students - Nguyen, Thanh Thi; Nguyen, Lan Thi Ha; Duong, Thoan Thi; Trinh, Cuong Van; Bui, Loan Thi (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the implementation of extracurricular educational activities at the university, focusing on both management staff and student perspectives. It aims to assess the extent to which these activities achieve their intended objectives, evaluate the application of organizational principles, and identify areas for improvement. By analyzing both viewpoints, the study provides a comprehensive understanding of the effectiveness of extracurricular programs in fostering students' knowledge application, ethical development, and social competencies. A quantitative research design was employed, utilizing structured questionnaires to collect data from 50 managerial staff members and faculty administrators, 35 student union leaders and student affairs officers, and 330 students across various faculties. The survey was conducted over three months, from September to November 2020, using a four-point Likert scale to measure perceptions of extracurricular activity objectives and organizational principles. Descriptive statistical methods, including mean scores and ranking analysis, were used to analyze the data. The findings reveal that both management staff and students perceive extracurricular activities as beneficial, particularly in enhancing students' ability to apply knowledge to real-life problems, reinforcing moral values, and promoting social skills. However, awareness of policies, laws, and institutional regulations received the lowest ratings, indicating a gap in engagement with these aspects. Both groups highlighted the role of student organizations in facilitating extracurricular activities, but concerns were raised about the alignment of these programs with overall student development goals. The study underscores the importance of strategic alignment between extracurricular activities and institutional objectives to maximize their impact. While these programs effectively contribute to student growth, improvements in policy education, interdisciplinary collaboration, and structured assessment methods are needed. Strengthening these areas can enhance the relevance and effectiveness of extracurricular initiatives, fostering a holistic educational experience that prepares students for academic, professional, and personal success.